Hemodynamic response after injection of local anesthetics with or without adrenaline in adult Nigerian subjects undergoing simple tooth extraction - Olutayo James; Akinola L Ladeinde; Mobolanle O Ogunlew; Janet N. A. Ajuluchukwu; Wasiu L Adeyemo (Journal of Clinical Sciences, 2015)
Objective: This study was conducted to determine the changes in the blood pressure (BP) and the pulse rate (PR) of normotensive patients having dental extraction under the administration of 2% lignocaine local anesthetic with or without adrenaline. Materials and Methods: This prospective study was carried out on 325 consecutive normotensive patients who presented at the exodontia clinic of the Lagos University Teaching Hospital (LUTH), Lagos, Yoruba State, Nigeria from December 2004 to August 2005 for simple tooth extraction. The patients were randomly allocated into two groups according to the type of anesthetic solution employed. Group A had tooth extraction done under the administration of 2% lignocaine with adrenaline (1:80,000) while group B had tooth extraction done under the administration of 2% lignocaine local anesthetic without vasoconstrictor (plain lignocaine). Each patient had single tooth extracted. The following parameters were monitored in each of the surgical interventions: systolic blood pressure (SBP), diastolic blood pressure (DBP), and PR. Measurements were taken in the waiting room before surgery, during the surgery after local anesthesia, during tooth extraction, and 15 min after tooth extraction. Results: The sample consisted of 176 females and 149 males. Age range of the patients was 18-89 years with the mean age of 35.08 ± 15.60 years. The hemodynamic responses to lignocaine with adrenaline (1:80,000) and plain lignocaine essentially follow the same pattern in the study. There was no statistically significant difference between the measured parameters in the two groups after the administration of local anesthetics. Conclusion: This study, therefore, shows that there was no difference in the hemodynamic changes observed with the use of lignocaine with adrenaline or plain lignocaine during a simple tooth extraction in healthy adults.